THE IMPACT OF DESIGN BASED LEARNING TOWARDS SECONDARY STUDENTS' CREATIVE THINKING SKILL IN THE ELECTRICITY CONCEPT - Saraswati, Rizkia (2013)
The purpose of this study is to investigate the impact of design-based learning on students' academic achievement in the electricity concept. I examined nine of ninth grade students' science class in Mutiara Nusantara International School. Through this research the writer wanted to know the level and profiles of students' creative thinking skill. In the implementation, the students run six stages that included into design-based learning stages to make an electrical alarm system, using pretest-posttest and portfolio assessment as an alternative assessment. The method that appropriate used in data processing is quantitative descriptive research method with descriptive analysis genre. Descriptive research collects data in order to answer questions about the current status of the topic of study and uses formal instruments to study practices and concerns of a sample. Based on the data analysis, almost the entire course of design based learning accordance with the existing theory, both teams occupied level 3 in the creative thinking level, most of scores in the creative thinking skill aspects were varied, and the value of average normalized gain for the experiment class reach 0.511 that is meant it is included into medium category in the improvement of students' cognitive domain to the electricity concept. Based on the results, it can be concluded that the implementation of design based learning model has a superior performance in term of knowledge gain achievements in the core science concepts. Keywords: Design Based Learning, Creative Thinking Skill, Electricity Tujuan dari pembuatan skripsi ini adalah untuk meneliti dampak dari pembelajaran berbasis desain terhadap pencapaian akademik siswa pada konsep kelistrikan. Penulis menetapkan sebanyak sembilan siswa kelas sembilan di sekolah internasional Mutiara Nusantara. Melalui penelitian ini, penulis ingin mengetahui level dan profil keterampilan berpikir kreatif siswa. Pada pelaksanaannya seluruh siswa menjalankan enam tahap yang termasuk dalam pembelajaran berbasis desain dengan membuat sebuah sistem alarm, menggunakan pretest-posttest dan assesmen portfolio sebagai assesmen alternatif. Metode yang digunakan dalam pengolahan data adalah metode kuantitatif deskriptif. Penelitian deskriptif ini mengumpulkan data dengan tujuan untuk menjawab seluruh pertanyaan selama penilitian berlangsung dan menggunakan beberapa instrumen formal untuk digunakan terkait dengan sampel. Berdasarkan analisis data, hampir seluruh pembelajaran berbasis desain sesuai dengan teori yang ada, kedua tim mencapai level 3 dalam keterampilan berpikir kreatif, dan aspek keterampilan berpikir kreatif siswa yang ditampilkan oleh kedua tim bervariasi, dan nilai dari average normalized gain pada kelas ini adalah sebesar 0.511, yang artinya termasuk pada kategori medium dalam peningkatan domain kognitif siswa pada konsep kelistrikan. Berdasarkan seluruh hasil, dapat disimpulkan bahwa implementasi pembelajaran berbasis desain ini memiliki kinerja yang baik dalam pencapaian konsep sains. Kata Kunci: Pembelajaran Berbasis Desain, Keterampilan Berpikir Kreatif, Kelistrikan.